Corruption and constitutionalism in Africa: revisiting control measures and strategies - Fombad, Charles Manga; Steytler, N. C. (Stellenbosch handbooks in African constitutional law, 2020)
This edited collection explores the endemic corruption that has spread into every aspect of social, economic, and political life which is at the heart of the crisis of constitutionalism in Africa and draws attention to the need for remedial action.